Cannabinoid Modulation of Emotion, Memory, and Motivation - Campolongo, Patrizia.; Campolongo, Patrizia.; Fattore, Liana.; Fattore, Liana. (Springer New York : Imprint: Springer, 2015)
The endocannabinoid system consists of cannabinoid receptors, their endogenous lipid ligands (endocannabinoids) and the enzymatic machinery for their synthesis and degradation. In the brain, endocannabinoids regulate ion channel activity and neurotransmitter release and thereby contribute to various aspects of brain function, including memory, reward and emotions. Their ability to modulate synaptic efficacy has a wide range of functional consequences and provides unique therapeutic possibilities. Unprecedented advances have been made in the understanding of the role of endocannabinoids in the regulation of the emotional brain over the past few years. However, a comprehensive book encompassing all these aspects is still lacking. The book will provide an overview of the role played by the endocannabinoid system in the regulation of emotional processes with particular emphasis on the modulation of memory and reward for emotionally arousing events and for the regulation of motivational aspects in cannabis use.